2010
DOI: 10.3109/09637486.2010.506432
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index and phenolics of partially-baked frozen bread with sourdough

Abstract: Different lactic acid bacteria starters were used to prepare sourdough to make partially-baked frozen wholemeal wheat bread. The sourdough was prepared with a pure culture of Lactobacillus plantarum or with commercial starters containing Lactobacillus brevis combined with Saccharomyces cerevisiae var. chevalieri (LV4), Lactobacillus fermentum (PL1), or Lactobacillus fermentum with phytase (PL3). We determined the acetic and lactic acid concentrations in sourdough, bread chemical composition, total phenolics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 38 publications
4
38
1
2
Order By: Relevance
“…It is therefore likely that the acidity present in many of the fruits evaluated contributed to the findings of the present study Novotni et al, 2011;Brand-Miller et al, 2014).…”
Section: Discussionmentioning
confidence: 57%
“…It is therefore likely that the acidity present in many of the fruits evaluated contributed to the findings of the present study Novotni et al, 2011;Brand-Miller et al, 2014).…”
Section: Discussionmentioning
confidence: 57%
“…The concentration of polyphenols in carob fruits depends strongly on genetic, environmental and extraction methods and ranges between 45–5376 mg gallic acid equivalents per 100 g [53,54,55]. In carob fruits, phenolic compounds are found as free, as bound or as soluble conjugated forms; Dubravka et al reported that the majority of carob phenolics are covalently bound to the dietary fibers [56]. In addition, carob germ and carob seed are rich sources of phenolic compounds [1].…”
Section: Functional Chemical Components Of Carob Fruitmentioning
confidence: 99%
“…skrobi opornej [3,23,28]. Nie jest ona trawiona przez enzymy układu pokarmowego człowieka, tym samym produkty ją zawierające charakteryzują się obniżoną wartością indeksu glikemicznego [22].…”
Section: Wyniki I Dyskusjaunclassified